Civic Nationalism, Universalism and War Crimes - Erözden, Ozan (Institute for Philosophy and Social Theory, University of Belgrade, 2016)
During the first phase of Croatia’s transition to democracy, which started with the death of Franjo Tudjman in the end of 1999, the prosecution of war crimes and crimes against humanity allegedly committed by the members of Croatian armed forces and paramilitary during the conflict between 1991 and 1995 was one of the most important issues on the political agenda. During this period SDP, which was the biggest partner of a coalition government, assumed a universalist approach to the issue, advocating impartial criminal prosecution regardless of ethnic background of perpetrators. While in line with the party’s civic nationalist stance, this policy encountered serious challenges as the United Nations War Crimes Tribunal (the ICTY) issued indictments for officials that were considered as heroes of Croatian Homeland War. By examining the case of SDP, this paper aims to discuss whether civic nationalism’s universalist theoretical premises are politically applicable during and/or in the aftermath of violent conflicts generated with extensive reference to ethnic identities.
The case of Croatian Social Democrat Party (SDP)
Keywords: Social democratic party; Civic nationalism; Croatia; War crimes